Monitoring glacier variations in the Urubamba and Vilcabamba Mountain Ranges, Peru, using “Landsat 5” images - Suarez, Wilson (2013)
The Urubamba and Vilcabamba mountain ranges are two geological structures belonging to the Andes in the southern part of Peru, which is located in the tropical region. These mountain ranges are especially located within the transition area between the Amazon region (altitudes close to 1’000 m a.s.l.) and the Andes. These mountains, with a maximum height of 6’280 m a.s.l. (Salkantay Snow Peak in the Vilcabamba range), are characterized by glaciers mainly higher than 5000 m a.s.l. Here we present a study on the evolution of the ice cover based on “Landsat 5” images from 1991 and 2011 is presented in this paper. These data are freely available from the USGS in a georeferenced format and cover a time span of more than 25 years.